The preferred conformation of erythro- and threo-1,2-difluorocyclododecanes - Wang, Yi; Kirsch, Peer; Lebl, Tomas; Slawin, Alexandra M. Z.; O'Hagan, David (Beilstein Journal of Organic Chemistry, 2012)
Cyclododecane adopts a square-like structure with corner and edge CH2 groups. In this study erythro- and threo-1,2-difluorocyclododecanes were prepared to explore whether the two vicinal C–F bonds, with different relative configurations, preferably locate at corner/edge or edge/edge locations. Conformational analysis comparing the diastereoisomers was explored by using a combination of 19F{1H} NMR spectroscopy, computational studies and, in the case of the threo isomer, X-ray structural analysis. In the lowest energy conformers for both diastereoisomers the vicinal C–F bonds are located corner/edge, rather than edge/edge. These structures avoid placing a C–F bond endo into the ring, and appear to benefit from C–CHF–C angle widening, which relaxes 1,4-H,H transannular interactions.
Keywords: alicyclic chemistry; conformational analysis; cyclododecane; 19F NMR; organo-fluorine chemistry; transannular interactions

(untitled) - Dunitz, J. D.; Shearer, H. M. M. (Helv. Chim. Acta, 1960)

(untitled) - Bürgi, H.-B.; Dunitz, J. D. (Helv. Chim. Acta, 1993)

(untitled) - Dale, J. (Acta Chem. Scand., 1973)

Stereochemistry of Organic Compounds - Eliel, E. L.; Wilen, S. H. (Wiley-Interscience, 1994)

(untitled) - Anet, F. A. L.; Rawdah, T. N. (J. Am. Chem. Soc., 1978)

(untitled) - Atavin, E. G.; Mastryukov, V. S.; Allinger, N. L.; Almenningen, A.; Seip, R. (J. Mol. Struct., 1989)

(untitled) - Skibinski, M.; Wang, Y.; Slawin, A. M. Z.; Lebl, T.; Kirsch, P.; O’Hagan, D. (Angew. Chem., Int. Ed., 2011)

(untitled) - Dasaradhi, L.; O'Hagan, D.; Petty, M. C.; Pearson, C. (J. Chem. Soc., Perkin Trans. 2, 1995)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Goodman, L.; Gu, H.; Pophristic, V. (J. Phys. Chem. A, 2005)

(untitled) - Souza, F. R.; Freitas, M. P.; Rittner, R. (J. Mol. Struct., 2008)

(untitled) - Michel, D.; Schlosser, M. (Tetrahedron, 2000)

(untitled) - Nicoletti, M.; O'Hagan, D.; Slawin, A. M. Z. (J. Am. Chem. Soc., 2005)

(untitled) - Durie, A. J.; Slawin, A. M. Z.; Lebl, T.; Kirsch, P.; O'Hagan, D. (Chem. Commun., 2011)

(untitled) - Eyring, H. (J. Chem. Phys., 1935)